Final Report for a 1998 National Teaching Development Grant (Individual) : CoChem : An Innovative Approach to Interdisciplinary Advanced Chemistry Teaching. - Jamie, Joanne (Committee for University Teaching and Staff Development, 2000)
This is a final report for a 1998 National Teaching Development Grant (Individual) funded by the Committee for University Teaching and Staff Development. The report summarises the project and outlines ways that the modular laboratory program for students has been implemented. Project evaluation and future directions are discussed.